205 Runs of homozygosity and analysis of inbreeding depression. (5th December 2019) - Sumreddee, Pattarapol; Toghiani, Sajjad; Roberts, Andrew J; Hay, El H; Aggrey, Samuel E; Rekaya, Romdhane
Abstract: Pedigree information was traditionally used to assess inbreeding. Availability of high-density marker panels provides an alternative to assess inbreeding, particularly in the presence of incomplete and error-prone pedigrees. Assessment of autozygosity across chromosomal segments using runs of homozygosity (ROH) is emerging as a valuable tool to estimate inbreeding due to its general flexibility and ability to quantify chromosomal contribution to genome-wide inbreeding. Unfortunately, identifying ROH segments is sensitive to the parameters used during the search process. These parameters are heuristically set, leading to significant variation in the results. The minimum length required to identify a ROH segment has major effects on the estimation of inbreeding, yet it is arbitrarily set. Understanding the rise, purging, and the effects of deleterious mutations requires the ability to discriminate between ancient and recent inbreeding. However, thresholds to discriminate between short and long ROH segments are largely unknown. To address these questions, an inbred Hereford cattle population of 785 animals genotyped for 30, 220 SNPs was used. A search algorithm to approximate mutation loads was used to determine the minimum length of ROH segments. It consisted of finding genome segments with significant differences in trait means between animals with high and low autozygosity intervals at certain threshold values. The minimum length was around 1 Mb for weaning and yearling weights and ADG, and 2.5 Mb for birth weight. Using a model-based clustering algorithm, a mixture of three Gaussian distributions was clearly separable, resulting in three classes of short (< 6.16 Mb), medium (6.16–12.57 Mb), and long (>12.27 Mb) ROH segments, representing ancient, intermediate, and recent inbreeding. Contribution of ancient, intermediate and recent to genome-wide inbreeding was 37.4%, 40.1% and 22.5%, respectively. Inbreeding depression analyses showed a greater damaging effect of recent inbreeding, likely due to purging of old highly deleterious haplotypes.